CONTINUING EDUCATION FOR TEACHERS AND INCLUSIVE PRACTICES IN LIGHT OF NEUROSCIENCES: AN INTERVENTION ANALYSIS IN THE TREATMENT OF ADHD (REMUNOM, 2026)
This study analyzes the contributions of a continuing education program for teachers, based on neuroscience, to the improvement of inclusive teaching practices aimed at serving students with Attention Deficit Hyperactivity Disorder (ADHD). It is assumed that the consolidation of inclusive education requires not only regulatory adjustments, but also the epistemological and methodological qualification of teaching work, especially with regard to understanding the neurobiological processes involved in learning. The research, which used a qualitative approach complemented by descriptive quantitative analysis, was conducted with 15 teachers in the final years of elementary school through focus groups, a training course, and pre- and post-intervention assessments. Data analysis, based on content analysis techniques, showed a significant increase in teachers' understanding of the relationship between executive functions, attention, and learning, as well as greater confidence in adopting differentiated teaching strategies. The results indicate that the articulation between neuroscience and continuing education favors the construction of more consistent inclusive practices, by shifting the understanding of ADHD from an exclusively behavioral perspective to a grounded pedagogical approach. It can be concluded that training programs based on neuroeducation can contribute to reducing exclusionary practices and strengthening pedagogical mediation in heterogeneous contexts, although their effectiveness depends on institutional continuity and integration with teacher professional development policies.